The Impact of Energy Subsidy Reform on Economic Growth in Egypt Over the Period from 2013 to 2020 - Abdallah Mostafa, Mohammed Galal (International Journal of Energy Economics and Policy, 2021)
In most developing countries, and the Middle East region in particular, "Energy Subsidy" is an issue of special importance for policymakers. To this day, there are no conclusive results concerning the possible impacts of the energy subsidies reform on economic growth. On this basis, this current study aims to examine the impacts of the energy subsidies reform on the economic growth in Egypt. To achieve the study’s objective, the impacts of the energy subsidies reform have been divided into the following: a) indirect impacts: estimated through the use of AMOS OR WARP PLS program, and b) direct impacts: determined on basis of the Autoregressive Distributed Lag Model. So, this study evaluates the indirect effects of energy subsidy reform on economic growth. So, this current study has concluded that the energy subsidies reform in Egypt has significant negative effects on economic growth in both the short and long terms, whether they are direct or indirect impacts. Therefore, this research recommends that when it comes to reducing the energy subsidies, the Egyptian government shall adopt a lenient approach, to avoid the relevant negative impacts; thus, such measures shall be executed over many stages that extend for a longer period of time, with the provision of a social fund that supports the low-income people more comprehensively. Keywords: Energy subsidy reform, economic growth, Egypt JEL Classifications: O4, C5, Q4 DOI: https://doi.org/10.32479/ijeep.11210